THE EFFECT OF LEARNING FACILITIES TOWARD STUDENTS’S LEARNING OUTCOMES OF CLASS X AND XI SOCIAL ON ECONOMICS OF SMA 3 PEKANBARU - Yuli Fitriana; Sumarno '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
The research aims to investigate the influence of learning facilities to thelearning outcomes of students at class X and XI IPS on economic subjects in SMANegeri 3 Pekanbaru. Based on a survey that has been done by the writer at theschool, there are skill students in class XI IPS who have not reached the KKM.While students in the class X most still many who have not reached the KKM oneconomic subject which can be based on semester exam brade in 2012/2013. Theresearch has been done to X dan XI IPS students in SMA Negeri 3 Pekanbaru. Thenumber of entire class or population of X dan XI IPS class are 448 students and thesample in this research is 82 students. The data collection techniqe is using simplerandom sampling. Data collected by using questionnaire that contain the questionsabout the students facilities at school or at home/ students individual property that isthen distributed to students as the respondents in this research, and this data is calledprimer data. As for the secondary data in the form of the value of the secondsemester of academic year 2012/2013 on economic subjects. In this study the datawere analyzed using simple linear regression. Test used in the analysis requirementsof normality and linearity test data. Hypothesis testing is done by using T test and itcan be seen that the calculated value of T (11.130)> T table value (1.664), the errorrate of 5%. Analysis of the calculation results in a simple regression equationobtained a constant value of 21 421 and a regression coefficient or b values obtainedfor 17 352. And the coefficient of determination (R ^ 2) obtained by the R value of0.780 and the coefficient of determination (R Square) of 0.608.Word:Learning facilities, Students’s Learning Outcomes